Conquering ‘enemies within':a moral therapy for healing nigerian entrepreneurship (2020)
The paper posits that many scholars interrogated several challenges facing Nigerian Entrepreneurs from 'outside perspectives' ranging from economics, socio-economic, cultural, to psychology with insignificant attention paid to ‘inside perspectives’ that are practically inherent in the personalities and profdes of Nigerian Entrepreneurs. The inside perspectives', which this paper describes as enemies within’ are spiritualisation of business, godly financial spending, substituting business time for religious programme, problem of trust, bad character and unhealthy competition among entrepreneurs. They were discussed thoroughly and methods of conquering them were suggested as moral therapy for healing Nigerian entrepreneurship.